The relationship between aggression and ability emotional intelligence: The role of negative affect. - Megías-Robles, Alberto; Gómez-Leal, Raquel; Gutiérrez-Cobo, María José; Cabello-González, Rosario; Fernández-Berrocal, Pablo (Elsevier, 2018)
This study aimed to contribute to the understanding of the mechanisms underlying the relationship between aggressive behaviour and individual levels of ability emotional intelligence (EI). Three hundred and ninety-five participants took part in this study. Participants were assessed on ability EI, negative affect (NA), and aggression by the Mayer–Salovey–Caruso Emotional Intelligence Test, the Positive and Negative Affect Schedule, and the Buss–Perry Aggression questionnaires, respectively. The results revealed a negative relationship between aggression and ability EI, but this relationship depended on multiple factors: the type of EI branches and aggression dimensions, the influence of NA, and gender. Emotional management ability showed a direct relationship with aggression, while emotional perception ability presented an indirect relationship with aggression through the effect of NA. These EI abilities were related to different aggression dimensions, highlighting the direct relationship with physical aggression. Moreover, gender differences showed that women possess greater EI abilities, higher levels of NA, less aggressive behaviour, and a lower relationship between NA and aggression compared with men. This research offers a better understanding of the psychological processes explaining aggression. The inclusion of our findings in the design of prevention and treatment programs could be of great help in the control of aggressive behaviour.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/16060
Keywords: Agresividad (Psicología); Diferencias sexuales (Psicología); Madurez afectiva; Aggression; MSCEIT; Negative affect; Emotional intelligence; Gender differences